The image of Russians and Russia in the minds of Polish students of the Russian language before and after the Russian aggression in Ukraine - Teshajev Sunderland, Eva (Glottodidactica, 2024)
For centuries, Polish-Russian relations have been turbulent. However, the young generation of Poles born after 1989 seemed to be less burdened by history than their parents, and showed some interest in the Russian language and culture, for which the steadily increasing number of students taking a degree in Russian studies was proof. The Russian aggression in Ukraine, however, has dramatically worsened Polish-Russian relations again. The aim of this article is to investigate if, and to what extent the Ukraine war has influenced the attitude towards, and the image of Russia in the minds of young Poles who chose to take a degree in Russian studies prior to the war. In order to research this topic, I conducted a survey at Adam Mickiewicz University in Poznań and compared the answers to a similar survey conducted in 2017. The results of the data analysis suggest that students who did their degree in 2017 had a relatively more positive image of Russia and its’ people, and that both the image of Russia and Russians is considerably more negative amongst the participants of the recent survey.